Trauma Tactics: Rethinking Trauma Education for Professional Nurses. Issue 4 (July 2016) - Garvey, Paula; Liddil, Jessica; Eley, Scott; Winfield, Scott
Abstract : According to the National Trauma Institute (2015), trauma accounts for more than 180, 000 deaths each year in the United States. Nurses play a significant role in the care of trauma patients and therefore need appropriate education and training (L.Patient, 2007 ). Although several courses exist for trauma education, many nurses have not received adequate education in trauma management (B.Armstrong, 2013 ; L.Patient, 2007 ). Trauma Tactics, a 2-day course that focuses on high-fidelity human patient simulation, was created to meet this educational need. This descriptive study was conducted retrospectively to assess the effectiveness of the Trauma Tactics course. Pre- and postsurveys, tests, and simulation performance were used to evaluate professional nurses who participated in Trauma Tactics over a 10-month period. Fifty-five nurses were included in the study. Pre- and postsurveys revealed an increase in overall confidence, test scores increased by an average of 2.5 points, and simulation performance scores increased by an average of 16 points. Trauma Tactics is a high-quality course that provides a valuable and impactful educational experience for nurses. Further research is needed to evaluate the long-term effects of Trauma Tactics and its impacts on quality of care and patient outcomes.